Maintaining Efficient Operation of Low-Yield Wells During the Development of the Cenomanian Deposit - E. I. Inyakina; E. E. Levitina; A. V. Plazun; M. J. Z. Alsheikhly (Наука. Инновации. Технологии, 2024)
The object of the study is the Cenomanian deposit during the period of self-damping of wells. The accumulation of droplet liquid causes destruction of the rock skeleton and increases pressure loss during gas movement in the well, which affects the dynamics of the operating stock indicators. The experience of introducing pipes with a diameter of 114 mm at the Yamburgskoye field increased the water-free period of well operation without self-pressure. Based on the available information on the development of the Cenomanian deposit, a forecast was made of the likely beginning of self-suffocation of the well stock for the current period until 2030. Thus, the results and forecast estimates showed that in almost all analyzed wells, conditions for water removal are maintained for a period of up to five years, and in some, waterless conditions will remain for more than ten years. Thus, it is recommended to replace the lift string for each specific well by analyzing its operating conditions and using temporary killing technology using special lightweight solutions that do not lead to contamination of the bottom-hole zone of the formation. During the development of Cenomanian deposits in the fields of the Far North, in the process of reducing reservoir pressure, fluid accumulation occurs at the bottom. For efficient operation of wells, it is necessary to create optimal technological operating modes for water removal and carry out measures to limit water inflows. Having analyzed various methods of combating self-squeezing of wells, it was concluded that in the conditions of development of the Yamburg field, the most effective is to replace lift pipes with pipes of smaller diameter, which allows increasing the rate of gas rise into the tubing and leads to self-cleaning of wells from liquid accumulating at the bottom.